DAMPAK DESENTRALISASI FISKAL TERHADAP INDEKS PEMBANGUNAN MANUSIA DI INDONESIA (Studi pada Kabupaten/Kota Kurun Waktu 2015-2021) - Sofilda, Eleonora; Hamzah, Muhammad Zilal; Nurhaida, Dida (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
This study intends to investigate the impact of fiscal decentralization on Indonesia's Human Development Index through per-capita income. The study's focus is on Indonesia's 415 Regencies and Cities from 2015 to 2021. Certain government spending indicators are employed in panel data regression as independent variables using Eviews 9.00. Secondary data were collected from the Central Bureau of Statistics (BPS) and the Ministry of Finance (MoF). The results of model 1 show that of the eight variables used to see their effect on per capita income, there are six variables that have a favorable impact, namely health budget allocations, public service functions, social protection functions, village funds, regional independence and investment, while education fund allocations and the economic function is unable to increase per capita income in Indonesia. The outcomes of model 2 demonstrate that components of model 1's influence on per capita income have a favorable impact on Indonesia's Human Development Index.